2005
DOI: 10.1197/j.aem.2004.02.532
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Emergency Medicine Resident Debt Status and Financial Planning Preparedness

Abstract: Objectives: Most resident physicians accrue significant financial debt throughout their medical and graduate medical education. The objective of this study was to analyze emergency medicine resident debt status, financial planning actions, and educational experiences for financial planning and debt management. Methods: A 22-item questionnaire was sent to all 123 Accreditation Council on Graduate Medical Education-accredited emergency medicine residency programs in July 2001. Two follow-up mailings were made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…9,16 In our survey, we found that those residents with the most medical school debt were most likely to "strongly agree" or "agree" that they were going to moonlight during their training. What was fascinating, however, was that the opportunity to moonlight at a particular residency or fellowship did not influence one group over another to attend a particular residency or fellowship.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…9,16 In our survey, we found that those residents with the most medical school debt were most likely to "strongly agree" or "agree" that they were going to moonlight during their training. What was fascinating, however, was that the opportunity to moonlight at a particular residency or fellowship did not influence one group over another to attend a particular residency or fellowship.…”
Section: Discussionmentioning
confidence: 92%
“…[7][8][9][10] We then developed a web-based survey instrument, evaluated its content validity by using a small number of residents, fellows, and faculty (n ϭ 10) to complete sample surveys, and refined the tool to ensure that the tool worked well, questions were understandable, and the time to take the survey was reasonable (5-10 minutes). There were 53 multiple-choice questions and 1 optional free text box on the final survey (Appendix, see Supplemental Digital Content 1, http://links.lww.com/AA/A368).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have called for medical schools and residency programs to increase financial awareness among medical students and residents (Glaspy, 2005;Greene & Puder, 2002;J. M. Teichman et al, 2001;J.…”
Section: Discussionmentioning
confidence: 99%
“…For medical students, the major reasons for taking on a part-time job are to supplement their income and the positive educational experience. The amount of study debt has been correlated in other studies with part-time employment (4,(10)(11)(12). Subsequent studies should therefore explore student study debt and the socioeconomic status of the dental hygiene students.…”
Section: Discussionmentioning
confidence: 91%